Effect of isotonic solutions and peptide adsorption on zeta potential of porous silicon nanoparticle drug delivery formulations - Kaasalainen, Martti; Mäkilä, Ermei; Riikonen, Joakim; Kovalainen, Miia; Järvinen, Kristiina; Herzig, Karl-Heinz; Lehto, Vesa-Pekka; Salonen, Jarno (International journal of pharmaceutics, 2012)
Zeta potential of porous silicon nanoparticles is highly dependent on the nature of the loaded peptide and the isotonic medium. Recently, highly promising results considering the use of porous silicon (PSi) nanoparticles as a controlled and targeted drug delivery system have been published. Drugs are typically loaded into PSi nanoparticles by electrostatic interactions, and the drug-loaded nanoparticles are then administered parenterally in isotonic solutions. Zeta potential has an important role in drug adsorption and overall physical stability of nanosuspensions. In the present study, we used zeta potential measurements to study the impact of the formulation components to the nanosuspension stability. The impact of medium was studied by measuring isoelectric points (IEP) and zeta potentials in isotonic media. The role of drug adsorption was demonstrated with gastrointestinal peptides GLP-1(7-37) and PYY (3-36) and the selection of isotonic additive was demonstrated with peptide-loaded PSi nanoparticles. The results show the notable effect of isotonic solutions and peptide adsorption on zeta potential of PSi nanosuspensions. As a rule of thumb, the sugars (sucrose, dextrose and mannitol) seem to be good media for negatively charged peptide-loaded particles and weak acids (citric- and lactic acid) for positively charged particles. Nevertheless, perhaps the most important rule can be given for isotonic salt solutions which all are very poor media when the stability of nanosuspension is considered.